LEGAL STUDY OF THE MECHANISM OF APPLICATION FOR ADOPTION OF AN ADULT CHILD BASED ON MEDAN DISTRICT COURT DECISION NUMBER 703/PDT.P/2025/PN.MDN - Shela Hernita; Nursariani Simatupang (Inspiring Law Journal, 2026)
Child adoption is a legal act that aims to provide protection and certainty of status for children, as regulated in Law Number 35 of 2014 concerning Child Protection and Government Regulation Number 54 of 2007 concerning the Implementation of Child Adoption. Normatively, child adoption is only permitted for children who are not yet 18 years old. However, in judicial practice, there are applications for child adoption submitted when the child has reached adulthood, as occurred in the Medan District Court Decision Number 703/Pdt.P/2025/PN.Mdn. This study aims to analyze: (1) the requirements for child adoption according to the provisions of Indonesian positive law; (2) the mechanism for applications for the adoption of adult children based on the decision; and (3) the judge's legal considerations in granting applications for the adoption of children who are 20 years old.This research uses a normative legal research type with a statute approach and a case approach.Data collection was conducted through a literature review by reviewing laws and regulations, court rulings, and relevant legal literature. The data were analyzed qualitatively based on laws and regulations, legal literature, and court rulings. The results of the study indicate that although Government Regulation No. 54 of 2007 limits the maximum age of adopted children to 18 years, judges still grant applications based on considerations of the existing foster care relationship since childhood, as well as the principle of the child's best interests and the need for legal certainty in population administration. This ruling confirms that judicial practice sometimes utilizes the space for legal interpretation to fulfill the benefit and protection of children, even though it is not entirely in line with normative boundaries.